Psychiatric Emergency Response: The Integration of Nursing Care, Laboratory Diagnostics, and Mental Health Protocols - Al-Shaibani, Fahad Mishai; aljohani , Sultan awad; alsehli, Fahad abdulhadi; almutiri, Mohammed Khaled; Alharbi, Mohammed abdulhamid abdulrahim; Alhajoj, Ibrahim Hassn; Raddadi, Reem Mohammed; Ezzi , Ali ebrahim; sulaiaman, Yasmin madani; Alharbi, Nader Abdullah Mufarrij (Journal of Ecohumanism, 2024)
Psychiatric emergency response is a critical aspect of mental health care that requires a well-integrated approach combining nursing care, laboratory diagnostics, and mental health protocols. This study explores the effectiveness of a multidisciplinary model in psychiatric emergency settings by systematically reviewing existing literature and evaluating the impact of these integrated components. The methodology follows a qualitative research design, employing a systematic review of peer-reviewed articles, policy reports, and clinical guidelines published between 2010 and 2025. The study utilizes thematic analysis to identify recurring patterns and categorize findings into key areas such as crisis intervention, patient stabilization, interprofessional collaboration, and policy implementation. The results highlight the necessity of standardized psychiatric emergency protocols to ensure consistency in response, reduce treatment delays, and improve patient safety. The study underscores the vital role of psychiatric nurses, who play a pivotal role in crisis intervention, patient stabilization, and interdisciplinary coordination. Findings also demonstrate that laboratory diagnostics significantly enhance diagnostic accuracy, enabling healthcare providers to differentiate psychiatric symptoms from underlying medical conditions. Additionally, the research emphasizes the importance of interprofessional collaboration among emergency physicians, laboratory technicians, and mental health specialists to facilitate holistic patient care. The study identifies challenges such as inconsistencies in psychiatric emergency protocols across different healthcare systems and gaps in psychiatric nursing education. Recommendations include investing in continuous professional training for psychiatric nurses, implementing standardized laboratory diagnostic procedures in emergency settings, and fostering interdisciplinary teamwork to enhance psychiatric crisis management. Future research should focus on evaluating the real-world impact of these findings and exploring emerging technologies such as artificial intelligence and telepsychiatry to further improve psychiatric emergency response.